Three Independent Mesial Canals in a Mandibular Molar: Four-Year Followup of a Case Using Cone Beam Computed Tomography. (15th April 2013) - de Paula, Adrianne Freire; Brito-Júnior, Manoel; Quintino, Alex Carvalho; Camilo, Carla Cristina; Cruz-Filho, Antônio Miranda; Sousa-Neto, Manoel Damião
Abstract : Endodontic treatment of mandibular molars is challenging because of variable root canal morphology. The nonsurgical endodontic management of a mandibular first molar presenting an independent middle mesial canal is reported. After coronal access, additional clinical inspection of the mesial canals' orifices and their interconnecting groove using an endodontic explorer and 4.5× loupes enabled the identification of the middle mesial canal orifice. All root canals were chemomechanically prepared and filled. The tooth was asymptomatic and functional after 4 years of followup. Cone beam computed tomography (CBCT) images revealed normal periapical status and three-dimensional (3D) anatomical aspects of the root canal system.